Maintenance low dose systemic glucocorticoids have limited impact on bone strength and mineral density among incident renal allograft recipients: a pilot prospective cohort study - Pérez-Sáez, M; Herrera, S; Prieto-Alhambra, D; Vilaplana, L; Nogués, X; Vera, M; Redondo-Pachón, D; Mir, M; Güerri, R; Crespo, M; Díez-Pérez, A; Pascual, J (Elsevier, 2018)
Soon after kidney transplant (KT), a decrease in parathormone and bone mineral density (BMD) occur, but little is known on the impact of KT on novel bone quality parameters including trabecular bone score (TBS) and bone material strength index (BMSi). We aimed to study BMD, TBS and BMSi in the first year after KT, in patients not treated with any bone therapy. A cohort including 36 patients underwent KT on a low-glucocorticoid-dose protocol (5 mg daily-prednisone from post-operative-day 42 onwards) and was observed for 12 months prospectively. At 3 months, phosphorus and parathormone decreased, while calcium increased. We also observed at 3 months a transient mild 2.9% bone loss at femoral neck (BMD change 0.752 ± 0.15 vs 0.730 ± 0.15; p = 0.004), but no change at either spine or total hip. Both TBS and BMSi remained stable. At 12 months, lumbar (but not total hip or femoral neck) BMD slightly decreased by 2.1% vs baseline (0.950 ± 0.15 vs 0.930 ± 0.5; p = 0.046), while TBS and BMSi remained unmodified. In KT patients on low-dose glucocorticoids and no bone therapy, there were small BMD decreases at femoral neck (at 3 months) and lumbar spine (at 12 months), but no change in either TBS or BMSi. Low-dose post-KT glucocorticoid treatment shows limited impact on bone, supporting steroid-restrictive protocols.